Evolution of traditional Chinese medicine registration review and approval policies: research based on the LDA topic model - Lu, Kaidi; Xie, Ming; Sun, Wanping; Liu, Yiming (Frontiers in Public Health, 2025)
IntroductionThe economic expansion of the Traditional Chinese Medicine (TCM) industry has prompted the Chinese government to introduce a series of policies focused on the registration review and approval of TCM. These policies aim to provide scientific and practical guidance for the innovation, protection, and progress of TCM. Although scholars have conducted detailed studies on the quantitative assessment of Traditional Chinese Medicine Registration Review and Approval Policies(TCMRAPs), Research on the evolution analysis of these policies is still relatively lacking.MethodsThe evolution of TCMRAPs was analyzed using the Latent Dirichlet Allocation (LDA) topic model.ResultsThe results show that the scope of concern of the TCMRAPs in China is vast. TCMRAPs demonstrate their uniqueness at each stage, and over time, they have exhibited a development trend from a basic framework to standardization and refinement.DiscussionThis study provides a reference for the subsequent formulation of TCMRAPs in China. Also, it offers an assessment method and theoretical reference for other countries in formulating their own policies for the drugs.